2016
DOI: 10.1104/pp.16.00850
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Spacing Safeguards Stomatal Dynamics by Facilitating Guard Cell Ion Transport Independent of the Epidermal Solute Reservoir

Abstract: Stomata enable gaseous exchange between the interior of the leaf and the atmosphere through the stomatal pore. Control of the pore aperture depends on osmotic solute accumulation by, and its loss from the guard cells surrounding the pore. Stomata in most plants are separated by at least one epidermal cell, and this spacing is thought to enhance stomatal function, although there are several genera that exhibit stomata in clusters. We made use of Arabidopsis (Arabidopsis thaliana) stomatal patterning mutants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 58 publications
(76 reference statements)
3
36
0
1
Order By: Relevance
“…The reduced stomatal opening in the genotypes with patterning defects was reportedly due to mechanical failure of the guard cells of one or more of the following: (1) impaired guard cell function due to a lack of ions from epidermal cells for osmotic function (Outlaw, 1989); (2) competition between adjacent guard cells through increasing turgor pressure, creating opposing forces between the two guard cells; and (3) disruption to the signaling mechanism that determines the structure of the guard cells . Papanatsiou et al (2016) confirmed that incorrect stomatal patterning impacted guard cell dynamics in the cluster mutant too many mouths and showed that this was accompanied by a reduction in K + accumulation in Figure 1. Interspecific diversity of (A) g s , (B) A, and (C) intrinsic water use efficiency (W i ) of Phaseolus vulgaris, Vicia faba, Triticum aestivum, and Nicotiana tabacum in response to a diurnal (8-h) sinusoidal variation of light intensity (from 0 to 2,000 mmol m 22 s 21 ).…”
Section: Influence Of Stomatal Patterning On Leaf-level Gas Exchangesupporting
confidence: 59%
“…The reduced stomatal opening in the genotypes with patterning defects was reportedly due to mechanical failure of the guard cells of one or more of the following: (1) impaired guard cell function due to a lack of ions from epidermal cells for osmotic function (Outlaw, 1989); (2) competition between adjacent guard cells through increasing turgor pressure, creating opposing forces between the two guard cells; and (3) disruption to the signaling mechanism that determines the structure of the guard cells . Papanatsiou et al (2016) confirmed that incorrect stomatal patterning impacted guard cell dynamics in the cluster mutant too many mouths and showed that this was accompanied by a reduction in K + accumulation in Figure 1. Interspecific diversity of (A) g s , (B) A, and (C) intrinsic water use efficiency (W i ) of Phaseolus vulgaris, Vicia faba, Triticum aestivum, and Nicotiana tabacum in response to a diurnal (8-h) sinusoidal variation of light intensity (from 0 to 2,000 mmol m 22 s 21 ).…”
Section: Influence Of Stomatal Patterning On Leaf-level Gas Exchangesupporting
confidence: 59%
“…The one-cell-spacing rule between any two stomata, which may derive from requirements for solute reservoirs or potassium ion channel function, as well as space requirements for other cell types such as epidermal hairs (Bergmann and Sack, 2007;Papanatsiou et al, 2016) explain why stomatal index is more highly conserved between different environments than stomatal density (the number per unit area). As with increases in vein density, increasing stomatal density while holding stomatal size constant has a diminishing effect on total conductance, as the concentration gradients around each pore increasingly overlap (Ting and Loomis, 1965;Lehmann and Or, 2015).…”
Section: Alternative Constraints: Stomatal Structure and Cell Sizementioning
confidence: 99%
“…In Arabidopsis, the control of stomatal patterning has been shown to directly influence plant gas exchange, photosynthetic function, and productivity Franks and Casson, 2014;Franks et al, 2015;Lehmann and Or, 2015;Papanatsiou et al, 2016). In particular, correct spacing via alterations to stomatal size and density ensures optimal guard cell pore control and faster responses to environmental cues .…”
Section: Does Stomatal Patterning Assist Stomatal Function In Mosses?mentioning
confidence: 99%